TRENDS AND INNOVATIONS IN COSMETIC MARKETING - Roman Ustymenko (Izdevnieciba "Baltija Publishing", 2023)
This study delves into the intricacies of the evolution of cosmetic marketing, shedding light on emerging trends that are redefining how cosmetic products are sold and perceived. It aims to identify the main trajectories of the cosmetics market and thoroughly explore their potential impact on future marketing strategies. The methodologies used in this study include statistical analysis to decipher market dynamics and forecasts, an in-depth literature review to track market narratives, and a comparative approach to understand the relative impact of each trend. Digging deeper into the results, a major trend was the focus on transparency and clarity of product ingredients. Consumers are leaning towards brands that demonstrate unambiguous ingredient lists and transparent sourcing and production practices. The second key trend is the rapid integration of artificial intelligence and big data technologies into cosmetic marketing. Brands are using AI-powered tools to provide personalised product recommendations, predictive marketing, and improve customer experience. In addition, the previously ignored male demographic is becoming a focus, requiring products and marketing campaigns tailored to male sensibilities and needs. The surge in demand for multifunctional cosmetic products, i.e., those that combine multiple benefits, highlights the fourth trend. Consumers are now gravitating towards products that offer multiple benefits by combining skincare and cosmetic benefits. Ultimately, brand loyalty, underpinned by ethical and sustainable practices, is seen as the linchpin of future marketing strategies. The practical implications of this research are multifaceted. For companies operating in the cosmetics market, understanding these trends is not only useful, but also necessary to adapt their strategies to keep them in sync with consumer expectations and ongoing market changes.